SIKAP ORGANISASI KEMASYARAKATAN ISLAM TERHADAP UNDANG-UNDANG NOMOR 17 TAHUN 2013 TENTANG ORGANISASI KEMASYARAKATAN DAN PERPU NOMOR 2 TAHUN 2017 (Perspektif Studi Kebijakan Dakwah) - Aziz, Mokhamad Abdul (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2017)
Freedom of association, assembly and expression is a part of human rights guaranteed by the 1945 Constitution of the State of the Republic of Indonesia. This freedom also includes the propagation of religious teachings as an ideology for transformation to real life. For Muslims, especially da'i certainly have great ideals for the realization of a prosperous fair society that is directed by Allah SWT. It can be fought, one of which can be through social organization.During the 72 years of independent Indonesia, several regulations issued by the government to regulate the system and mechanisms of mass organizations have added controversy to Islamic mass organizations. In the new order, some organizations threatened to be dissolved and not recognized for rejecting the sole principle of Pancasila. The dynamic continues until the reform era. This can be an afterthought for the da'wah perpetrators, especially those who take the path of the organization to pay more attention to the basic aspects of administrative formation with respect to the state / government, because it will subsequently be very influential on the sustainability of da'wah in the future.